The motivational climate perceived by young soccer players regarding their coaches, parents, and peers on sport optimal functioning: a cluster analysis - Natalia Martínez-González; Francisco L. Atienza-González; Lorena González-García; Isabel Balaguer (Frontiers in Psychology, 2025)
The aim of this study was (a) to describe the perceived motivational climate profiles created by coaches, parents, and peers of young football players, and (b) to analyse the implications of these profiles on goal orientations, motivation, psychological needs, and indicators of well- and ill-being. The participants were 876 football players (M = 13.57; SD = 1.17) who completed a multi-section questionnaire at the beginning of the sports season. Cluster analyses identified four profiles (empowering, disempowering, high mixed, low mixed) based on youth perceptions of empowering and disempowering climates created by coaches, parents, and peers. Multivariate analyses, controlling for gender and age, revealed that those young players categorized in the most adaptive profiles (high empowering climates and low disempowering climates) demonstrated optimal functioning, including task orientation, higher autonomous motivation, need satisfaction, and vitality. Conversely, those in the most maladaptive profile (low empowering climates and high disempowering climates) experienced the worst consequences (high levels of ego orientation, controlled motivation, no motivation, need frustration, physical and emotional exhaustion). Regarding mixed profiles, although the analyses reveal that combining empowering and disempowering behaviors limits the benefits of empowering climates, and low involvement hinders athletes’ development, future explorations are necessary to better interpret these profiles. As a whole, the results highlight the importance of considering the combined roles of coaches, parents, and peers, and suggest that interventions aimed at fostering empowering behaviors and reducing disempowering ones across these social agents may help support youth athletes’ optimal functioning.